1995
DOI: 10.1001/jama.1995.03520260071035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Screening Mammography

Abstract: Screening mammography significantly reduces breast cancer mortality in women aged 50 to 74 years after 7 to 9 years of follow-up, regardless of screening interval or number of mammographic views per screen. There is no reduction in breast cancer mortality in women aged 40 to 49 years after 7 to 9 years of follow-up. Screening mammography may be effective in reducing breast cancer mortality in women aged 40 to 49 years after 10 to 12 years of follow-up, but the same benefit could probably be achieved by beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 802 publications
(135 citation statements)
references
References 38 publications
2
122
0
11
Order By: Relevance
“…A meta-analysis of available literature from 1966 to 1993 suggested that annual mammography in women 50 to 74 years of age was shown to reduce breast-cancer related mortality by approximately 26% within 7 to 9 years of screening initiation. 19 The mortality benefits of screening mammography in women 40 to 74 years of age have also been supported by the US Preventive Services Task Force based on a recent analysis of the available literature. 20,21 This task force concluded that the overall balance of potential benefits of screening mammography versus potential harms improves with increasing age.…”
Section: Cancer Detection and Screeningmentioning
confidence: 98%
“…A meta-analysis of available literature from 1966 to 1993 suggested that annual mammography in women 50 to 74 years of age was shown to reduce breast-cancer related mortality by approximately 26% within 7 to 9 years of screening initiation. 19 The mortality benefits of screening mammography in women 40 to 74 years of age have also been supported by the US Preventive Services Task Force based on a recent analysis of the available literature. 20,21 This task force concluded that the overall balance of potential benefits of screening mammography versus potential harms improves with increasing age.…”
Section: Cancer Detection and Screeningmentioning
confidence: 98%
“…1 Reductions in mortality from breast cancer observed in England and Wales and in Finland are partly attributable to nationwide breast cancer screening programmes. 2,3 Considerable international experience has amply demonstrated that to obtain an efficient breast cancer screening programme, the entire screening process must be organised, that is, include proper training and accreditation of radiologists for mammography screening, technical quality assurance of mammography complying with well-known standards (e.g., de Wolf and Perry 4 ), an invitation-reinvitation system, mammography screening offered to women Ն50 years old, double reading of mammograms and monitoring of screening data with the possibility of matching these data with a population-based cancer registry to evaluate the programme sensitivity.…”
mentioning
confidence: 99%
“…También se ha demostrado que la mejor forma de hacer detección temprana del cáncer de mama es a través de un programa organizado para tamizar aspectos mamográ cos en la población (4,5). Por el contrario, existe evidencia muy controversial sobre la e cacia de la detección temprana con programas basados en la autoexploración mamaria y el examen clínico de los senos (6)(7)(8).…”
Section: Materiales Y Métodosunclassified